2013
DOI: 10.1136/heartjnl-2013-304129
|View full text |Cite
|
Sign up to set email alerts
|

The association of genetic variants of matrix metalloproteinases with abdominal aortic aneurysm: a systematic review and meta-analysis

Abstract: A common SNP within the MMP3 promoter region, previously suggested to increase MMP3 expression, appears to be a moderate risk factor for AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 33 publications
3
44
0
6
Order By: Relevance
“…The meta-analysis of 8 SNPs selected from the studies in which 58 SNPs within MMPs and TIMPs were investigated in abdominal aortic aneurism (AAA) pinpoint the significant association of only MMP-3 rs3025058 with AAA presence [115]. Another one, published the same year, which was investigated several genes in AAA presented the similar results for MMP-3 rs3025058 [116].…”
Section: Mmp-3supporting
confidence: 54%
“…The meta-analysis of 8 SNPs selected from the studies in which 58 SNPs within MMPs and TIMPs were investigated in abdominal aortic aneurism (AAA) pinpoint the significant association of only MMP-3 rs3025058 with AAA presence [115]. Another one, published the same year, which was investigated several genes in AAA presented the similar results for MMP-3 rs3025058 [116].…”
Section: Mmp-3supporting
confidence: 54%
“…They have identified various associations of some significance, but the vast majority of the studies included have analysed populations of less than 150 individuals. Further meta-analyses of gene-association studies have identified positive associations for the following SNPs: MMP-3 rs3025058,33 MMP-2 rs243865,34 MMP-13 rs2252070,34 elastin rs2071307,34 C reactive protein rs3091244,35TGF β rs764522 and rs1036095 36. A recent meta-analysis (in press) from our group has not confirmed previously identified putative associations for the ACE inhibitors rs3025058, MMP-3 rs3025058, nitric oxide synthase rs1799752 and methylenetetrahydrofolate reductase rs1801133 SNPs 37.…”
Section: Genetic Studiesmentioning
confidence: 99%
“…Molecular imaging targeted at the determinants of AAA expansion and rupture appears particularly promising in this regard (2). Matrix metalloproteinase (MMP) activation is a main pathophysiologic feature of AAA and is believed to be closely related to aneurysm progression and risk of rupture (3,4). Accordingly, molecular imaging of MMP activation may be a useful tool for AAA risk stratification.…”
mentioning
confidence: 99%